Substrate stiffness and oxygen availability as regulators of mesenchymal stem cell differentiation within a mechanically loaded bone chamber. - KELLY, DANIEL (My University, 2014)
M echanical stimuli such as tissue deformation and fluid flow are often implicated as regulators of mesenchymal stem cell (MSC) differentiation during regenerative events in vivo . However , in vitro studies have identified several other physical and biochemical environmental cues , such as substrate stiffness and oxygen availability, as key regulators of stem cell fate . Hypotheses for how MSC differentiation is regulated in vivo can be either corroborated or rejected based on the ability of in silico models to accurately predic t spatial and temporal patterns of tissue differentiation observed experimentally . The goal of this study was to employ a previously de veloped computational framework to test the hypothesis that substrate stiffness and oxygen availability regulate stem cel l differentiation during t issue regeneration within an implanted bone chamber. To enable a prediction of the oxygen levels within the bone chamber, a lattice model of angiogenesis was implemented where blood vessel progression was depend e nt on the local me chanical environment . The model successfully predict ed key aspects of MSC differentiation, including the correct spatial development of bone, marrow and fibrous tissue within the unloaded bone chamber . The model also successfully predicted chondrogenesis w ithin the chamber upon the application of mechanical loading. This study provides further support for the hypothesis that substrate stiffness and oxygen availability regulate stem cell differentiation in vivo . Th ese simulations also highlight the indirect role that mechanics may play in regulating MSC fate by inhibiting blood vessel progression and hence disrupting oxygen availability within regenerating tissues
PUBLISHED
Keywords: Mesenchymal Stem Cell Differentiation; Next Generation Medical Devices